Novel Mannitol-Based Small Molecules for Inhibiting Aggregation of α-Synuclein Amyloids in Parkinson's Disease - Paul, Ashim; Zhang, Bo-Dou; Mohapatra, Satabdee; Li, Gao; Li, Yan-Mei; Gazit, Ehud; Segal, Daniel (Frontiers in Molecular Biosciences, 2019)
The aggregation of the amyloidogenic protein α-synuclein (α-Syn) into toxic oligomers and mature fibrils is the major pathological hallmark of Parkinson’s disease (PD). Small molecules that inhibit α-Syn aggregation thus may be useful therapeutics for PD. Mannitol and naphthoquinone-tryptophan (NQTrp) have been shown in the past to inhibit α-Syn aggregation by different mechanisms. Herein, we tested whether the conjugation of Mannitol and NQTrp may result in enhance efficacy towards α-Syn. The molecules were conjugated either by a click linker or via a PEG linker. The effect of the conjugate molecules on α-Syn aggregation in vitro was monitored using Thioflavin T fluorescence assay, circular dichroism, transmission electron microscopy and Congo red birefringence assay. The conjugate molecules were found to be more effective than the two parent molecules and as effective as a mixture of the two. Increasing the length of the linker to three PEG units resulted in superior efficacy. The conjugate molecules attenuated the disruptive effect of α-Syn on artificial membrane of Large Unilamellar Vesicles as monitored by dye leakage assay. The conjugates were found to be non-cytotoxic and reduced toxicity of α-Syn towards SH-SY5Y neuroblastoma cells. These novel designed entities can be attractive scaffold for the development of therapeutic agents for PD.